Assessment of arsenic distribution, bioaccessibility and speciation in rice utilizing continuous extraction and in vitro digestion. (1st June 2021) - Wang, Pengfei; Yin, Naiyi; Cai, Xiaolin; Du, Huili; Fu, Yaqi; Geng, Ziqi; Sultana, Sharmin; Sun, Guoxin; Cui, Yanshan
Graphical abstract: Highlights: Of the total As, 87.5–94.5% was in rice protein and 5.0–9.8% in rice starch. The order of As amount in proteins: glutelin > globulin > albumin > prolamin. Bioaccessible As and As in protein fraction was positively correlated. Almost all As(V) dissolved in the small intestinal phase. In the colon, the As bioaccessiblity was significantly decrease. Abstract: Rice, a staple food for half the world's population, easily accumulates arsenic (As). Research on As distribution in rice protein and starch and its relationship with rice As bioaccessibility remains limited. This study investigated As distribution, chemical composition, As bioaccessibility and speciation in rice by continuous extraction and in vitro digestion. Of the total As, 87.5–94.5% was in rice protein and 5.0–9.8% in rice starch. The As amount in different protein fractions decreased as follows: glutelin > globulin > albumin > prolamin. As(V), As(III) and DMA in rice were more bioaccessible in the small intestinal phase than the gastric phase, and almost all As(V) dissolved in the small intestinal phase. Bioaccessible As in gastrointestinal digestive solution and As mass in protein fractions (albumin, globulin, and glutelin) were significantly positively correlated ( p < 0.05). These results illuminate the bioaccessibility of As to humans consuming As-contaminated rice and avoid overassessment.